Environmental correlates of intellectual achievement - Fernandez, Rosario V. (1976)
The predictive value of two aspects of the home environment for general intelligence as measured by two entrance tests (ET1 and ET2) and academic achievement as measured by the teachers' grades in Language, Reading and Mathematics are the foci of the study. The purpose of this study is to identify the environmental correlates of the intellectual ability of selected Prep students of the Ateneo Grade School.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Keywords: Academic achievement